A study of truly incompressible and weakly compressible Smoothed Particle Hydrodynamics methods to model incompressible flows with free surfaces. Issue 1 (December 2014) - Beck, Florian; Hirschler, Manuel; Niecken, Ulrich; Eberhard, Peter
Abstract The Smoothed Particle Hydrodynamics (SPH) method is a meshless discretization method for solving, e.g., the Navier‐Stokes equations. By now, it is used for hydraulic problems as well as for solid bodies. In general, there are two distinguishable approaches for incompressible fluid flows. One is called weakly compressible SPH (WCSPH) and the other is called truly incompressible SPH (ISPH). The main difference between these two approaches is the way of pressure evaluation. In WCSPH, a state equation is used, while in ISPH the pressure Poisson equation is solved. Each approach has its advantages as well as its disadvantages, for example the complexity of the numerical algorithm for WCSPH is smaller than for ISPH, but the pressure field is more accurate for ISPH. In this work, two representative examples are studied. The simulations were performed with two different codes, one developed at the Institute of Engineering and Computational Mechanics and one at the Institute of Chemical Process Engineering. It is the aim of this work to show some properties of WCSPH and ISPH as well as to compare two different implementations that, in detail, are very complex. (© 2014 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)